Confiance en soi et métamorphose éducative - Didier Moreau (Nantes Université, 2018)
This article investigates how, in education, self-reliance has been underpinned by trust in the educator. By distinguishing confidence and seduction, one returns to education its original project to lead the subjects towards the emancipation. At first, this project is examined through Seneca's theory of friendship. But we must understand the aporia of modernity which builds self-reliance over distrust of authority. The solution of Gadamer's hermeneutics is questioned in the educational relationship. The third problem is the destruction of self-reliance by educational institutions. Emerson's essays are a guide to grasp this process and the remedies he advocates for rebuilding self-reliance. Finally, in Proust's work, considered as a novel of formation, one can read the practice the most completed of self-reliance building.